Correlation analysis of vaccination coverage, positivity rate, and community mobility rate on COVID-19 effective reproductive rate: SIR modeling study from Indonesia - Meirina Nur Asih Susanti; Siti Nurrochmah; Lucky Radita Alma; Supriyadi Supriyadi (CV Rezki Media, 2025)
Background: Effective Reproduction Rate (Rt) is used to evaluate COVID-19 transmission; although Tegal City has the lowest cumulative cases in Central Java, the spread of the virus remains rapid. Intervention efforts are carried out through vaccination coverage, positivity rate, and level assessment as a shared responsibility to reduce the transmission rate. Objectives: The purpose of this study was to estimate the spread of COVID-19 with the intervention and to determine whether there is a correlation between the COVID-19 Rt Number and vaccination coverage, positivity rate, and level assessment situation in Tegal City. Methods: Observational quantitative research design. The type of research used was SIR (Susceptible Infected Removed) mathematical modeling and descriptive analysis through an ecological study approach and Spearman correlation statistical analysis. Results: The results of the study showed a decrease in the number of cases of vulnerable and infected subpopulations after public health interventions, followed by the results that the positivity rate and level assessment situation were significantly correlated with the strength of the relationship powerful to the Covid-19 Effective Reproductive Rate with values (r=0.856; p=0.00) and (r=-0.712; p=0.00), while vaccination coverage was not statistically significantly correlated with a value of (r=-0.209; p=0.137). Conclusions: The positivity rate and COVID-19 level assessment situation were statistically significantly correlated to the effective reproductive rate of COVID-19 in Tegal City with a strong correlation. Meanwhile, vaccination coverage did not correlate statistically with effective reproductive rate. Further studies must evaluate the effectiveness of combined interventions (vaccination + testing + mobility restriction) in various epidemiological settings.